2003
DOI: 10.1089/153623103322637706
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Peripheral Blood Mononuclear Cells in Piglets Used as an Animal Model for Staphylococcal Enterotoxin Exposures

Abstract: We have used piglets as an animal model for studying the toxic effects of staphylococcal enterotoxins (SEs). Piglets are easy to handle, easy to carry out vital measurements, inexpensive, and more importantly, express remarkably similar pathological symptoms and responses to SE intoxication as humans at comparable doses. Microarray analyses are used to study the effect of many infections on gene expression profile in peripheral blood mononuclear cells. This high throughput application offers detailed depiction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Hammamieh et al 70 have developed useful data on variability among pigs within peripheral blood mononuclear cells (PBMC). Using a human cDNA membrane array, they measured the PBMC expression profiles of ten Yorkshire piglets.…”
Section: Current Expression Profiling Results In Porcine Tissues Amentioning
confidence: 99%
See 1 more Smart Citation
“…Hammamieh et al 70 have developed useful data on variability among pigs within peripheral blood mononuclear cells (PBMC). Using a human cDNA membrane array, they measured the PBMC expression profiles of ten Yorkshire piglets.…”
Section: Current Expression Profiling Results In Porcine Tissues Amentioning
confidence: 99%
“…The immune response is highly complex, with multiple tissues and cell types communicating information that is contextual and changes during early inflammatory stages as well as during inflammatory resolution and the adaptive immune response, and changes can also be long-term through immune memory. Hammamieh et al 70 have developed useful data on variability among pigs within peripheral blood mononuclear cells (PBMC). Using a human cDNA membrane array, they measured the PBMC expression profiles of ten Yorkshire piglets.…”
Section: Current Expression Profiling Results In Porcine Tissues and Cells Using Microarraysmentioning
confidence: 99%
“…Therefore, piglets are being increasingly used as models to study many human diseases as well as human biological phenomenon. Hence, such studies of gene expression variations of animal models used to study human pathogens are important to interpret the final outcome of expression studies [47].…”
Section: Host-pathogen Interactionmentioning
confidence: 99%
“…Animal studies have shown that 75% of the toxin administered to primates localizes to renal proximal tubule epithelial cells (RPTEC), which possess a glycosphingolipid receptor for SEB and express apoptotic markers in response to the toxin. These cells also secrete potent vasoconstrictors, endothelins, which play an important role in vascular tone regulation [16][17][18][19]. A highly collaborative research effort within the DARPA program was aimed to reconstruct a model of the pre-apoptosis processes involved in the response to SEB.…”
Section: Host-pathogen Interaction Sebmentioning
confidence: 99%